Synthesis and characterization of fluorinated azadipyrromethene complexes as acceptors for organic photovoltaics - Etheridge, Forrest S.; Fernando, Roshan J.; Pejić, Sandra; Zeller, Matthias; Sauvé, Geneviève (Beilstein Journal of Organic Chemistry, 2016)
Homoleptic zinc(II) complexes of di(phenylacetylene)azadipyrromethene (e.g., Zn(WS3)2) are potential non-fullerene electron acceptors for organic photovoltaics. To tune their properties, fluorination of Zn(WS3)2 at various positions was investigated. Three fluorinated azadipyrromethene-based ligands were synthesized with fluorine at the para-position of the proximal and distal phenyl groups, and at the pyrrolic phenylacetylene moieties. Additionally, a CF3 moiety was added to the pyrrolic phenyl positions to study the effects of a stronger electron withdrawing unit at that position. The four ligands were chelated with zinc(II) and BF2+ and the optical and electrochemical properties were studied. Fluorination had little effect on the optical properties of both the zinc(II) and BF2+ complexes, with λmax in solution around 755 nm and 785 nm, and high molar absorptivities of 100 × 103 M−1cm−1 and 50 × 103 M−1cm−1, respectively. Fluorination of Zn(WS3)2 raised the oxidation potentials by 0.04 V to 0.10 V, and the reduction potentials by 0.01 V to 0.10 V, depending on the position and type of substitution. The largest change was observed for fluorine substitution at the proximal phenyl groups and CF3 substitution at the pyrrolic phenylacetylene moieties. The later complexes are expected to be stronger electron acceptors than Zn(WS3)2, and may enable charge transfer from other conjugated polymer donors that have lower energy levels than poly(3-hexylthiophene) (P3HT).
Keywords: dye; fluorine; near-IR absorber; non-fullerene acceptor; zinc(II) complex

(untitled) - Loudet, A.; Burgess, K. (Chem. Rev., 2007)

(untitled) - Palma, A.; Gallagher, J. F.; Müller-Bunz, H.; Wolowska, J.; McInnes, E. J. L.; O'Shea, D. F. (Dalton Trans., 2009)

(untitled) - Partyka, D. V.; Deligonul, N.; Washington, M. P.; Gray, T. G. (Organometallics, 2009)

(untitled) - Ge, Y.; O'Shea, D. F. (Chem. Soc. Rev., 2016)

(untitled) - Gorman, A.; Killoran, J.; O'Shea, C.; Kenna, T.; Gallagher, W. M.; O'Shea, D. F. (J. Am. Chem. Soc., 2004)

(untitled) - Byrne, A. T.; O'Connor, A. E.; Hall, M.; Murtagh, J.; O'Neill, K.; Curran, K. M.; Mongrain, K.; Rousseau, J. A.; Lecomte, R.; McGee, S.; Callanan, J. J.; O'Shea, D. F.; et al. (Br. J. Cancer, 2009)

(untitled) - Killoran, J.; Allen, L.; Gallagher, J. F.; Gallagher, W. M.; O'Shea, D. F. (Chem. Commun., 2002)

(untitled) - O'Connor, A. E.; Mc Gee, M. M.; Likar, Y.; Ponomarev, V.; Callanan, J. J.; O'Shea D, F.; Byrne, A. T.; Gallagher, W. M. (Int. J. Cancer, 2012)

(untitled) - Senevirathna, W.; Liao, J.-y.; Mao, Z.; Gu, J.; Porter, M.; Wang, C.; Fernando, R.; Sauvé, G. (J. Mater. Chem. A, 2015)

(untitled) - Mao, Z.; Senevirathna, W.; Liao, J.-Y.; Gu, J.; Kesava, S. V.; Guo, C.; Gomez, E. D.; Sauvé, G. (Adv. Mater., 2014)

(untitled) - Sauvé, G.; Fernando, R. (J. Phys. Chem. Lett., 2015)

(untitled) - Senevirathna, W.; Daddario, C. M.; Sauvé, G. (J. Phys. Chem. Lett., 2014)

(untitled) - Babudri, F.; Farinola, G. M.; Naso, F.; Ragni, R. (Chem. Commun., 2007)

(untitled) - Leroux, F.; Jeschke, P.; Schlosser, M. (Chem. Rev., 2005)

(untitled) - Pagliaro, M.; Ciriminna, R. (J. Mater. Chem., 2005)

Fluorine in Organic Chemistry - Chambers, R. D. (CRC Press, 2004)

(untitled) - Price, S. C.; Stuart, A. C.; Yang, L.; Zhou, H.; You, W. (J. Am. Chem. Soc., 2011)

(untitled) - Stuart, A. C.; Tumbleston, J. R.; Zhou, H.; Li, W.; Liu, S.; Ade, H.; You, W. (J. Am. Chem. Soc., 2013)

(untitled) - Yang, P.; Yuan, M.; Zeigler, D. F.; Watkins, S. E.; Lee, J. A.; Luscombe, C. K. (J. Mater. Chem. C, 2014)

(untitled) - Liang, Y.; Xu, Z.; Xia, J.; Tsai, S.-T.; Wu, Y.; Li, G.; Ray, C.; Yu, L. (Adv. Mater., 2010)

(untitled) - Zhou, H.; Yang, L.; Stuart, A. C.; Price, S. C.; Liu, S.; You, W. (Angew. Chem., Int. Ed., 2011)

(untitled) - Reichenbächer, K.; Süss, H. I.; Hulliger, J. (Chem. Soc. Rev., 2005)

(untitled) - Günes, S.; Neugebauer, H.; Sariciftci, N. S. (Chem. Rev., 2007)

(untitled) - Heremans, P.; Cheyns, D.; Rand, B. P. (Acc. Chem. Res., 2009)

(untitled) - Love, J. A.; Nagao, I.; Huang, Y.; Kuik, M.; Gupta, V.; Takacs, C. J.; Coughlin, J. E.; Qi, L.; van der Poll, T. S.; Kramer, E. J.; Heeger, A. J.; Nguyen, T.-Q.; et al. (J. Am. Chem. Soc., 2014)

(untitled) - Liu, Y.; Zhao, J.; Li, Z.; Mu, C.; Ma, W.; Hu, H.; Jiang, K.; Lin, H.; Ade, H.; Yan, H. (Nat. Commun., 2014)

(untitled) - Albrecht, S.; Janietz, S.; Schindler, W.; Frisch, J.; Kurpiers, J.; Kniepert, J.; Inal, S.; Pingel, P.; Fostiropoulos, K.; Koch, N.; Neher, D. (J. Am. Chem. Soc., 2012)

(untitled) - Carsten, B.; Szarko, J. M.; Son, H. J.; Wang, W.; Lu, L.; He, F.; Rolczynski, B. S.; Lou, S. J.; Chen, L. X.; Yu, L. (J. Am. Chem. Soc., 2011)

(untitled) - Yang, L.; Tumbleston, J. R.; Zhou, H.; Ade, H.; You, W. (Energy Environ. Sci., 2013)

(untitled) - Katz, H. E.; Lovinger, A. J.; Johnson, J.; Kloc, C.; Siegrist, T.; Li, W.; Lin, Y.-Y.; Dodabalapur, A. (Nature, 2000)

(untitled) - Sonar, P.; Ng, G.-M.; Lin, T. T.; Dodabalapur, A.; Chen, Z.-K. (J. Mater. Chem., 2010)

(untitled) - Shi, M.-M.; Chen, H.-Z.; Sun, J.-Z.; Ye, J.; Wang, M. (Chem. Commun., 2003)

(untitled) - Gao, L.; Senevirathna, W.; Sauvé, G. (Org. Lett., 2011)

(untitled) - Senevirathna, W.; Sauvé, G. (J. Mater. Chem. C, 2013)

(untitled) - delPozo, J.; Carrasco, D.; Pérez-Temprano, M. H.; García-Melchor, M.; Álvarez, R.; Casares, J. A.; Espinet, P. (Angew. Chem., Int. Ed., 2013)

(untitled) - Meana, I.; Albéniz, A. C.; Espinet, P. (Adv. Synth. Catal., 2010)

Introduction to Spectroscopy - Pavia, D. L.; Lampman, G. M.; Kriz, G. S.; Vyvyan, J. R. (Brooks, 2009)

(untitled) - Teets, T. S.; Partyka, D. V.; Updegraff, J. B.; Gray, T. G. (Inorg. Chem., 2008)

Macromolecular Crystallography, Pt A - Otwinowski, Z.; Minor, W. (1997)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Crystallogr., 2008)

SHELXTL, Bruker Advanced X-ray Solutions, Version 6.14 (2000)

Sheldrick (G. M. U. o. G.)

(untitled) - Hübschle, C. B.; Sheldrick, G. M.; Dittrich, B. (J. Appl. Crystallogr., 2011)